When is the best time to clamp the umbilical cord after a routine term vaginal delivery?. Issue 6 (June 2015) - Shih, Grace; Whited, Amber
Abstract : Evidence‐Based Answer : Delayed cord clamping (after 1–5 minutes) is associated with increased infant birth weight and hemoglobin concentration (Hgb), but it is also associated with an increased risk of jaundice and need for phototherapy (SOR: B, systematic review of RCTs with moderate risk of bias). Early cord clamping (before 1 minute) is associated with decreased iron stores at 3 to 6 months, but not at 12 months (SOR: C, disease‐oriented outcome). Evidence remains insufficient for or against delayed cord clamping in term infants (SOR: C, committee opinion).